1986
DOI: 10.1021/bi00369a042
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine hydroxylase from Chromobacterium violaceum is a copper-containing monooxygenase. Kinetics of the reductive activation of the enzyme

Abstract: Pterin-dependent phenylalanine hydroxylase from Chromobacterium violaceum contains a stoichiometric amount of copper (Cu2+, 1 mol/mol of enzyme). Electron paramagnetic resonance spectroscopy of the enzyme indicates that it is a type II copper-containing protein. The oxidized enzyme must be reduced by a single electron to be catalytically active. Dithiothreitol was found to be an effective reducing agent for the enzyme. Electron paramagnetic resonance data and kinetic results indicate the formation of an enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 40 publications
0
43
1
Order By: Relevance
“…The properties of the purified enzyme also differ from those described earlier (7,8,33). Prof. Benkovic has compared our results with those from his laboratory and concluded that two phenylalanine hydroxylases are present in C. violaceum.…”
Section: Addendumcontrasting
confidence: 64%
“…The properties of the purified enzyme also differ from those described earlier (7,8,33). Prof. Benkovic has compared our results with those from his laboratory and concluded that two phenylalanine hydroxylases are present in C. violaceum.…”
Section: Addendumcontrasting
confidence: 64%
“…It has been shown by EPR spectroscopy that dithiothreitol reduces the catalytic Cu(I1) to Cu(1) in phenylalanine hydroxylase isolated from Chromobucterium violaceum [33] and it has been suggested that dithiothreitol also reduces the enzyme-bound ferric iron to the ferrous form in the rat enzyme [2]. However, our present EPR studies under aerobic conditions with the bovine enzyme (Fig.…”
Section: Dithiothreitol Us An Inhibitor Ofphenylulanine Hydroxylasementioning
confidence: 59%
“…There is no evidence that the ferric enzyme is a catalytic intermediate; rather, these enzymes begin and end each catalytic cycle in the ferrous form. The C. violaceum enzyme has been isolated with copper instead of iron (20), and this observation led to the proposal that the bacterial enzyme does not require any metal for activity (21,22). More recently, C. violaceum PheH was shown to have an absolute requirement for iron for tyrosine formation (23), in agreement with the metal requirements of the eukaryotic enzymes.…”
Section: Methodsmentioning
confidence: 82%